Ferroptosis and its Role in Gastric Cancer - Gu, Renjun; Xia, Yawen; Li, Pengfei; Zou, Defang; Lu, Keqin; Ren, Lang; Zhang, Hongru; Sun, Zhiguang (Frontiers in Cell and Developmental Biology, 2022)
Gastric cancer (GC) is the fifth most common cancer and the third leading cause of cancer-related deaths worldwide. Currently, surgery is the treatment of choice for GC. However, the associated expenses and post-surgical pain impose a huge burden on these patients. Furthermore, disease recurrence is also very common in GC patients, thus, necessitating the discovery and development of other potential treatment options. A growing body of knowledge about ferroptosis in different cancer types provides a new perspective in cancer therapeutics. Ferroptosis is an iron-dependent form of cell death. It is characterized by intracellular lipid peroxide accumulation and redox imbalance. In this review, we summarized the current findings of ferroptosis regulation in GC. We also tackled on the action of different potential drugs and genes in inducing ferroptosis for treating GC and solving drug-resistance. Furthermore, we also explored the relationship between ferroptosis and the tumor microenvironment in GC. Finally, we discussed areas for future studies on the role of ferroptosis in GC to accelerate the clinical utility of ferroptosis-induction as a treatment strategy for GC.